2010
DOI: 10.1007/s10955-010-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Value Laws in Dynamical Systems for Non-smooth Observations

Abstract: Abstract. We prove the equivalence between the existence of a non-trivial hitting time statistics law and Extreme Value Laws in the case of dynamical systems with measures which are not absolutely continuous with respect to Lebesgue. This is a counterpart to the result of the authors in the absolutely continuous case. Moreover, we prove an equivalent result for returns to dynamically defined cylinders. This allows us to show that we have Extreme Value Laws for various dynamical systems with equilibrium states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 23 publications
2
87
0
Order By: Relevance
“…It first appeared in the pioneering paper of Collet, [72], which has been an inspiration for plenty of the research on this issue. Then the subject has been further addressed and developed in many subsequent contributions including [134,73,135,74,136,137,138,139,49,140,81,46,76,77,78,141,142,79,44].…”
Section: Emergence Of Extreme Value Laws For Dynamical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It first appeared in the pioneering paper of Collet, [72], which has been an inspiration for plenty of the research on this issue. Then the subject has been further addressed and developed in many subsequent contributions including [134,73,135,74,136,137,138,139,49,140,81,46,76,77,78,141,142,79,44].…”
Section: Emergence Of Extreme Value Laws For Dynamical Systemsmentioning
confidence: 99%
“…Alternatively, for observables φ : X → R tailored to the measure µ, so that µ{φ(x) > u n } is regularly varying in u, convergence rates can again be achieved. Such observables are considered in [136].…”
mentioning
confidence: 99%
“…It turns out that these are just two views on the same phenomena: there is a link between these two approaches. This link was already perceivable in the pioneering work of Collet, [9], however it has been formally proved in [13,14], where Freitas et al showed that under general conditions on the observable functions, the existence of HTS/RTS is equivalent to the existence of EVLs. These observable functions achieve a maximum (possibly ∞) at some chosen point ζ in the phase space so that the rare event of an exceedance of a high level occurring corresponds to an entrance in a small ball around ζ.…”
Section: Introductionmentioning
confidence: 92%
“…In [14], the authors carried the connection further to include more general measures, which, in particular, allowed the coauthors to obtain the connection in the random setting in [6]. For that, it was sufficient to use the skew product map to look at the random setting as a deterministic system and to take the observable ϕ • π : M × Ω → R ∪ {+∞} defined as in (2.6) with ϕ : M → R ∪ {+∞} as in [14, equation (4.1)].…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation